An in vitro study on dentin abrasion comparing two sonic toothbrushes with and without a coating versus an ADA reference manual toothbrush - Lea Walter; Amir Aminy; Stefan Zimmer; Mozhgan Bizhang (PLoS ONE, 2025)
This in vitro study evaluated dentin abrasion and surface roughness caused by two sonic toothbrushes with different filament coatings compared with those caused by a standard ADA reference manual toothbrush. Standardized dentin samples (n = 8 per group) were prepared from bovine incisors, embedded in acrylic blocks, polished, and hardness-verified using the Vickers method. A central brushing area was created by masking two reference zones with adhesive tape. Brushing simulations were performed in a laboratory device for 10,000 cycles at a load of 1.5 N using a toothpaste slurry (RDA 129) that was prepared at a 1:1.6 water-to-paste ratio. The tested toothbrushes included the ADA reference manual toothbrush (uncoated nylon filaments), the Curaprox Hydrosonic Pro toothbrush (uncoated PBT filaments), and the Curaprox Hydrosonic Black is White toothbrush (charcoal-coated PBT filaments). Dentin loss was measured by noncontact optical profilometry, and surface roughness was assessed by determining the Ra, Rq and Sa values. Data normality was verified using the Shapiro–Wilk test, and differences among groups were analyzed by one-way ANOVA with Bonferroni correction (α = 0.05). Compared with the ADA reference manual toothbrush, both the sonic toothbrushes caused significantly greater dentin loss (p < 0.001), with no significant difference between the sonic models (p > 0.05). The changes in roughness followed a similar pattern. These findings suggest that, under standardized laboratory conditions, sonic toothbrushes, regardless of the use of a filament coating, cause more dentin wear than a manual reference brush. Moreover, greater dentin abrasion was associated with less roughness, indicating an inverse relationship between tissue loss and surface roughness.